An interpretable approach for social network formation among heterogeneous agents - Yuan Yuan (Nature Portfolio, 2018)
Complex networks can be a useful tool to investigate problems in social science. Here the authors use game theory to establish a network model and then use a machine learning approach to characterize the role of nodes within a social network.